DILEMA DIVERSIFIKASI PRODUK: MENINGKATKAN PENDAPATAN ATAU MENIMBULKAN KANIBALISME PRODUK? - Lucius Hermawan (Universitas Trunojoyo Madura, 2015)
Product diversification is the company's efforts to increase sales through product diversification. Product diversification is intended to make the product last longer, leading to a product ready for consumption and use, fulfill the tastes, needs and expectations of customers, expand markets, facilitate transportation, employment, value-added, income and so forth. Necessary to diversify creativity, innovation, research, capital, promotion or marketing communication, assistance from government small and medium enterprises. But for companies that do not have a strong foundation, the diversification strategy will backfire for the company itself. Even a less innovative product diversification will be difficult to compete with competitors, the worse is the diversification of products will be consuming existing products (product cannibalism) and bring down each other.